HOT PRESS FORGING A Sustainable Direct Recycling of Aluminium - Nur Kamilah Yusuf; Mohd Amri Lajis; Azlan Ahmad (2019)
This book briefly discussed the direct recycling aluminium alloy as an impending secondary resource, executed via hot press forging process. It introduces innovative approach of recycling technique with energy practical understanding and cost-effective without arbitrating with the metallurgical processes. Besides that, the possibility of this recycled aluminium chip is forecasted to be employed as a secondary resource alternative to overcome the shortage of primary resources by utilizing the metal optimally and consequently lower the usage of raw metal. Furthermore, it will help to reduce the land use for mining and decrease air pollutant emission. This will be a better initiative to machining practitioners and industry as a support to our goverment on green technology and waste management.